Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
1. Given the functions f(x) = log₂(5x) and g(x) = 5ˣ - 2 only statement c is true
2. The solution of 3y² + 5y > -2 is a. x < –1 or x is greater than negative two thirds
1. How to find which statements are true.
Statement a
Since f(x) = log₂(5x) which is a logarithm function is undefined for (-∞, 0) and defined for (0, +∞) and g(x) = 5ˣ - 2 which is an exponential function is defined for (-∞, +∞).
Also, since f(x) is decreasing on the interval (0, 1/5) while g(x) decreases on the interval (-∞, 0). So, they have do not have a common interval on (0, 1).
So, statement a. Both f(x) and g(x) decrease on the interval of (–∞, 1).
is false
Statement b
Since f(x) = log₂(5x) which is a logarithm function is defined for (0, +∞) and g(x) = 5ˣ - 2 which is an exponential function is defined for (-∞, +∞).
So, the statement b Both f(x) and g(x) have the same domain of (0, ∞) is false
Statement c
Since f(x) = log₂(5x) which is a logarithm function has a range of (0, +∞). and g(x) = 5ˣ - 2 which is an exponential function is has a range of (-2, +∞).
So, they have a common interval of (0, +∞).
So, the statement c. Both f(x) and g(x) have a common range on the interval (–2, ∞) is true
Statement d
To find the x-intercept of f(x), we equate f(x) to zero.
So, f(x) = log₂(5x)
0 = log₂(5x)
2⁰ = 5x
1 = 5x
x = 1/5
To find the x-intercept of g(x), we equate g(x) to zero.
g(x) = 5ˣ - 2
0 = 5ˣ - 2
2 = 5ˣ
x = ㏒₅2
Since the x-intercept of f(x) = 1/5 and the x- intercept of g(x) = ㏒₅2. So, they do not have a common x - intercept.
So, the statement d. Both f(x) and g(x) have the same x-intercept of (1, 0) is false.
So, only statement c is true
2. How to find the solution of 3y² + 5y > -2?
3y² + 5y > -2
3y² + 5y + 2 > 0
3y² + 3y + 2y + 2 > 0
3y(y + 1) + 2(y + 1) > 0
(3y + 2)(y + 1) > 0
So, the boundary values are at
(3y + 2)(y + 1) = 0
(3y + 2) = 0 or (y + 1) = 0
y = -2/3 or y = -1
So, we require (3y + 2)(y + 1) > 0
For y < -1 say -2, (3y + 2)(y + 1) = (3(-2) + 2)((-2) + 1)
= (-6 + 2)(-2 + 1)
= -4(-1)
= 4 > 0
For -1 < y < -2/3 say -1/3, (3y + 2)(y + 1) = (3(-1/3) + 2)((-1/3) + 1)
= (-1 + 2)(-1 +3)/2
= 1(-2/2)
= -1 < 0
For y > -2/3 say 0, (3y + 2)(y + 1) = (3(0) + 2)((0) + 1)
= (0 + 2)(0 + 1)
= 2(1)
= 2 > 0
So, for (3y + 2)(y + 1) > 0, y < -1 or y > -2/3
So, the solution of 3y² + 5y > -2 is a. x < –1 or x is greater than negative two thirds
Learn more about logarithm and exponential function here:
https://brainly.com/question/3181916
#SPJ1
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.